Analisis Dampak Program Wirausaha Merdeka terhadap Minat Berwirausaha pada Mahasiswa - Didik Wahyu Nugroho; Siti Aisyah (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to describe the trend of entrepreneurship among students through the Independent Entrepreneurship (WMK) program implemented at the Muhammadiyah University of Surakarta in 2024. This program provides a forum for students to develop innovation and creativity in entrepreneurship through a series of activities such as workshops, internships and product expos. This program aims to improve practical skills, improve entrepreneurial thinking, and encourage innovation to overcome challenges in the business world. This study uses a descriptive qualitative approach, which allows researchers to study the subjective experiences of participants in a comprehensive manner. Interviews with a number of students who participated in the program were used as a method of data collection. The results of the study indicate that WMK improves students' entrepreneurial skills, from communication skills to business strategy development. In addition, this program facilitates the formation and development of businesses and provides students with the opportunity to build wider business networks and increase their confidence in conveying their products and ideas to the public. As part of the program, expo activities provide direct experience with the market. Overall, the WMK program has been shown to help students prepare themselves for the business world that demands creativity, innovation and optimal use of technology. According to this study, similar programs should be maintained to improve entrepreneurship in higher education institutions.